Symbiotic microbial community of cork oak stands under water gradient - Reis, Francisca Rodrigues (2017)
Global warming is increasing temperature and causing deregulation of water cycle (precipitation storms and long dry seasons) in the world. One of the most affected ecosystems is located in Mediterranean basin, where Portugal is included. Cork oak (Quercus suber L.)is one of the most important species for Portuguese forest ecosystem as well as for economic purposes. Although its tolerance to drought seasons, the rapid increase of temperature and decrease of water availability is causing a serious decline in cork oak populations. Drought stress is responsible for decreasing plant defenses and increases the vulnerability of tree pathogens. To face this problem, improvement of watering systems is not the best ecological and economic option. Microbial community present in soils is responsible for ecosystem sustainability, especially in forests. Symbiotic microorganisms are responsible not only for increasing plant defenses against pathogens as well as to uptake water and nutrients for the plant. In drought scenarios, where water availability is low, the presence of mycorrhizal fungi and nitrogen fixation bacteria is severely affected. Disturbances in rhizosphere community compromise root protection, where diseases caused by pathogens such as Phytophthora spp. can emerge. Enriching fungal and bacterial communities of cork oak stands prevent tree damage and therefore increases plant resistance to biotic stresses. Samples from 7 independent cork oak forests were collected in 5 different geographic locations (Gerês, Macedo de Cavaleiros, Vimeiro, Grândola and Moura) based on water availability. Samples from extreme conditions, the driest (Moura) and wettest (Gerês) places were sampled in two different sites. ECM community (root tips survey) and bacterial symbiont community (metabarcoding using Illumina platform) were accessed. Fungal and bacterial symbiotic communities are both influenced by water availability in the soil. Alentejo cork oak stands present lower fungal and bacterial diversity than northern ones. Russula, Tomentella, Cenococcum and Cortinarius are the main fungal colonizers, whereas Proteobacteria and Actinobacteria are the most abundant bacterial taxa identified. The obtained results will help to understand the importance of fungi/bacteria to drought tolerance in cork oak forest.